L'eta' dell'ossidiana di Pantelleria - Rapisarda, Massimo (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2007)
Obsidian is a volcanic glass which was highly prized in prehistoric times. Since its chemical composition depends on the local characteristics of the lava flow, several analytical methods have been employed to establish the provenance of the obsidian artefacts found in prehistoric sites, to identify the ways of the "ancient trade". These methods have become so successful that, besides distinguishing among different volcanoes, today it is even possible to discriminate among different flows of the same volcano. In fact the identification limit is not due to the method used, but to the intrinsic variability existing within the source. In the western Mediterranean, the two islands of Pantelleria and Lipari supplied all the material used for the artefacts found in Sicily and Tunisia. At Lipari, the differentiation among its sources has been made also on a time basis, with the Fission Tracks method, which determines the age of the mineral. At Pantelleria, chemical analytical methods have been able to distinguish among different layers of the same location. The first traces of obsidian use in the western Mediterranean are dated about 8,000 years ago, at the time of the eruptions of the Lipari flows, although the mineral was already available at Pantelleria. This date is confirmed in Sicily by a coherent set of findings, except for some oddly dated specimens. However, some clues like: the sizeable initial exploitation of Pantelleria obsidian, its gradual substitution almost everywhere by the Liparian mineral and the distribution of the Sicilian most ancient sites (seeming to indicate a diffusion process from west to east), hint that the exploitation of Pantelleria obsidian could have started earlier than today established. In principle the hypothesis is not absurd, if we remember that the first documented use of obsidian by Anatomically Modern Humans belongs to 125 thousand years ago on the shores of the Red Sea and that 65 thousand years ago, men showed their seafaring ability colonizing Australia, which was not connected to Asia by land. Moreover, an earlier seafaring would have been eased by the shorter marine distances. Note, for instance, that at the peak of the Ice Age, the sea level was about 130 metres lower than today and that Pantelleria, then the only provider of obsidian in the region, was much closer to the mainland, while the Straits of Sicily were much narrower and easily navigable. Due to the rapid cooling needed to its formation, it is unsurprising that, in the small islands of Pantelleria and Lipari, the obsidian flows are often hosted in cliffs plunging into the sea. Their orographic configurations suggest that some obsidian ores could be present in the underwater continuation of the cliffs. Owing to the sea level changes occurred since the end of the Ice Age, these possible underwater ores would have been emerged and accessible sometime in the past, with a precise correlation between depth and time of emersion. The possibility to attribute artefacts to a submarine flow would then set a time threshold to the period of the mineral collection, possibly pushing back the period of the first obsidian exploitation. The presence of such a missing source at Pantelleria is suggested by the existence of artefacts found in Sicily, having the overall characteristics of the Pantelleria mineral, but not belonging to any of the known flows. The peculiar orographic characteristic of the main Pantelleria source at Balata dei Turchi, made of stratified horizontal layers of obsidian in a cliff created by marine erosion suggest where to search. The obsidian layers are naturally ordered in temporal sequence, the oldest layer laying at the bottom of the sequence. Thus, should the unattributed artefacts denounce a Fission Tracks age older than the bottom flow, the hint for an underlying, possibly submerged, flow would be very strong.